Identifying preferred features of weight loss programs for adults with or at risk of type 2 diabetes: a discrete choice experiment with 3,960 adults in the U.K. - Buckell, J; Mitchell, CA; Fryer, K; Newbert, C; Brennan, A; Joyce, J; Jebb, SA; Aveyard, P; Guess, N; Morris, E (American Diabetes Association, 2024)
OBJECTIVE: To understand preferences for features of weight loss programs among adults with or at risk of type 2 diabetes in the U.K.